ANTIHYPERTENSIVE THERAPY AND CLIMACTERIC DISORDERS IN POSTMENOPAUSAL WOMEN - A. A. Kirichenko; Z. M. Tankieva (Рациональная фармакотерапия в кардиологии)
Aim. To study efficacy and tolerability of antihypertensive therapy with enalapril (Berlipril®, Berlin-Chemie AG/Menarini Group) and diltiazem (Altiazem® PP, Berlin-Chemie AG/Menarini Group) in postmenopausal women with arterial hypertension (HT) and climacteric disorders.Material and methods. 60 postmenopausal women (aged 56,8±3,9 y.o.) with HT of 1-3 degrees were included into the study. They were split in two groups. Patients of the first group (30 people) received enalapril (Berlipril®) 20 mg/daily, patients of the second group (30 people) – diltiazem (Altiazem® PP) 180-360 mg/daily. Observation period was 6 months. Ambulatory blood pressure monitoring (ABPM) was performed before treatment and after 3 weeks, 1, 3 and 6 months of therapy. Climacteric syndrome severity and urodynamic disorders was estimated as well as psychic status according to score of depression and anxiety.Results. Office and ambulance blood pressure decreased after 6 months of therapy in all patients of both groups. A number of complaints on headache and giddiness reduced significantly. Severity of climacteric syndrome also decreased. Enalapril (Berlipril®) monotherapy and especially combined therapy with hydrochlorothiazide led to aggravation of urodinamic disorders. On the contrary both monotherapy with diltiazem (Altiazem® PP) or its combination with hydrochlorothiazide had positive effect on urodinamics. Both therapies reduced depression and anxiety levels significantly.Conclusion. All spectrum of pharmacology effects should be taken into account during antihypertensive therapy of patients with climacteric disorders.